Issue Information. (30th December 2020) - Unknown
Abstract : SmartMat is dedicated to address the growing scientific interests in developing intelligent materials that can change significantly in a controlled fashion to external stimuli across the entire spectrum of materials based physics, chemistry, biology, electronics and engineering, helping to shape the smart society with a new generation of smart materials. SmartMat will present our readers with the most insightful and cutting‐edge research achievements and provide authors a highly efficient peer review and publishing production processes. SmartMat cordially invites you to submit original research, perspective, review articles, editorial, highlight and profiles. There are no article publication charges for the first three publication years of SmartMat .